The response of the microcirculation to cardiac surgery. Issue 1 (February 2016) - Kara, Atila; Akin, Sakir; Ince, Can
Abstract : Purpose of review: Cardiac surgery is associated with a wide range of microvascular derangements and with reduced tissue oxygenation. Although the macrohemodynamical targets during surgery may be achieved, the microcirculation may be damaged and remain dysfunctional. Direct observations of the microcirculation may enable more physiologically based approaches for diagnosis and treatment during cardiac surgery. Recent findings: Microcirculation is the final destination of blood flow to the tissues for oxygen transport. Direct visualization of the microcirculation using hand-held microscopy can be considered the gold standard for tissue perfusion since the movement of single red blood cells can be observed and quantified. A new generation microcirculation-monitoring device is called CytoCam-Incident -Dark-Field imaging. This device has a high-resolution imaging sensor and shows approximately 30% more capillaries than the devices of the previous generations. On-pump and off-pump cardiac surgeries have induced different mechanism whose impact can be differentiated by observation of the sublingual microcirculation. Colloids may provide a better volume expansion and microcirculatory improvement than crystalloids although crytaloids may be more affective for hydration, and blood transfusions improves microcirculatory oxygenation by filling previously empty capillaries and reducing diffusion distances between oxygen carrying red blood cell and the parenchymal cells. Summary: Direct visualization of the microcirculation using hand-held microscopy may provide the clinician the physiological feedback that is required for the early diagnosis and treatment of microcirculatory alterations during cardiac surgery. The coherence between the hemodynamic response of the macrocirculation and microcirculation during surgery seems to be essential.